2017
DOI: 10.1097/mpa.0000000000000924
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fatty Acid Binding Protein and Citrulline as Markers of Gut Injury and Prognosis in Patients With Acute Pancreatitis

Abstract: Intestinal fatty acid binding protein is a promising prognostic marker in acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The accuracies of D-lactate and I-FABP were high, and the AUCs of both biomarkers were >0.80. Compared with previous studies assessing intestinal ischaemia, these biomarkers exhibit variable accuracies (36)(37)(38)(39)(40)(41). Obviously, single biomarkers were not effective in the evaluation of intestinal mucosal barrier dysfunction given that each biomarker only partially reflects pathophysiological changes in intestinal function.…”
Section: Discussionmentioning
confidence: 98%
“…The accuracies of D-lactate and I-FABP were high, and the AUCs of both biomarkers were >0.80. Compared with previous studies assessing intestinal ischaemia, these biomarkers exhibit variable accuracies (36)(37)(38)(39)(40)(41). Obviously, single biomarkers were not effective in the evaluation of intestinal mucosal barrier dysfunction given that each biomarker only partially reflects pathophysiological changes in intestinal function.…”
Section: Discussionmentioning
confidence: 98%
“…[ 6 , 7 ] IFABP, a novel and objective biomarker of enterocyte injury, has been reported to be able to use for predicting outcomes of critical illness, such as acute decompensated heart failure, [ 3 ] cardiac arrest, [ 11 ] septic shock, [ 13 ] acute pancreatitis. [ 14 ] However, an association between IFABP and postoperative cardiac surgery patients has not been established. In this study, we found that serum IFABP level was well correlated with the AGI grade ( P < .001), and significantly higher in patients with inotropic score more than 10 ( P = .004), or patients who suffered from right ventricular dysfunction ( P = .016).…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Its circulating levels are very low in healthy individuals, but it rapidly releases into the systemic circulation upon enterocyte injury, and it is thus believed to be an early and useful marker for enterocyte injury. [ 12 ] Recently, elevated IFABP levels have been found in patients suffering from acute decompensated heart failure, [ 3 ] septic shock, [ 13 ] acute pancreatitis, [ 14 ] ulcerative colitis, [ 15 ] and have been reported as a promising sensitive marker for predicting clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal fatty acid binding proteins are increased in serum after intestinal mucosal injury related to a variety of causes, mainly of ischemic and inflammatory type. 8,16,17 Besides I-FABP, L-FABP is a useful plasma marker for the detection of intestinal injury. L-FABP shows a similar pattern of tissue distribution along the duodenal to colonal axis but a >40fold higher content than of I-FABP in each intestinal segment.…”
Section: Discussionmentioning
confidence: 99%